Loss of Id3 (Inhibitor of Differentiation 3) Increases the Number of IgM-Producing B-1b Cells in Ischemic Skeletal Muscle Impairing Blood Flow Recovery During Hindlimb Ischemia. Issue 1 (23rd November 2021) - Osinski, Victoria; Srikakulapu, Prasad; Haider, Young Min; Marshall, Melissa A.; Ganta, Vijay C.; Annex, Brian H.; McNamara, Coleen A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Neovascularization can maintain and even improve tissue perfusion in the setting of limb ischemia during peripheral artery disease. The molecular and cellular mechanisms mediating this process are incompletely understood. We investigate the potential role(s) for Id3 (inhibitor of differentiation 3) in regulating blood flow in a murine model of hindlimb ischemia (HLI). Approach and Results: HLI was modeled through femoral artery ligation and resection and blood flow recovery was quantified by laser Doppler perfusion imaging. Mice with global Id3 deletion had significantly impaired perfusion recovery at 14 and 21 days of HLI. Endothelial- or myeloid cell-specific deletion of Id3 revealed no effect on perfusion recovery while B-cell–specific knockout of Id3 (Id3 BKO ) revealed a significant attenuation of perfusion recovery. Flow cytometry revealed no differences in ischemia-induced T cells or myeloid cell numbers at 7 days of HLI, yet there was a significant increase in B-1b cells in Id3 BKO . Consistent with these findings, ELISA (enzyme-linked immunoassay) demonstrated increases in skeletal muscle and plasma IgM. In vitro experiments demonstrated reduced proliferation and increased cell death when endothelial cells were treated with conditioned media from IgM-producing B-1b cells and tibialis anterior muscles in Id3 BKO mice showed reduced density of total CD31 + and αSMA + CD31 + vessels. Conclusions: This study is the first to demonstrate a role for B-cell–specific Id3 in maintaining blood flow recovery during HLI. Results suggest a role for Id3 in promoting blood flow during HLI and limiting IgM-expressing B-1b cell expansion. These findings present new mechanisms to investigate in peripheral artery disease pathogenesis.